Saliva Versus Plasma Therapeutic Drug Monitoring of Valproic Acid in Jordanian Patients - Idkaidek, Nasir; Al-Tarawneh, Aya; Alshoaibi, Laith; Tuffaha, Haya; Zinati, Asma; Abdelqader, Majed; Al-Ghazawi, Ahmad; Rabayah, Ayman; Hamadi, Salim (Drug Research, 2024)
Therapeutic drug monitoring is used to ensure that medications are prescribed and administered according to safe doseage advice and for the purpose of achieving the desired therapeutic effects in patients. Several methods are used to perform therapeutic drug monitoring. However, there is insufficient evidence to currently support therapeutic drug monitoring of Valproic acid using salivary samples. The aim of this paper is to determine the feasibility of using salivary samples as a substitute for plasma samples for therapeutic drug monitoring of Valproic acid. In this study a total of 23 patients participated, with the mean age of 33.39. Salivary and plasma samples were collected and analysed to determine the peak and trough concentrations of Valproic acid for comparison between the two methods. Calibrated LC- MS/ MS was used to measure Valproic acid levels. Statistical analyses were performed using ANOVA test and ethical approval was obtained prior to sample collection. The results showed that saliva Valproic acid levels were less than that of plasma levels. There was no significant correlation between saliva and plasma level of Valproic acid (P>0.05). However, there was a significant correlation between the area under the curve for both saliva and plasma Valproic acid (P<0.05). Creatinine clearance was significantly correlated with peak plasma levels of Valproic acid (P<0.05). Albumin was significantly correlated with plasma levels of Valproic acid. There was also a significantly positive and moderate relationship between Log Saliva Cmax and Log plasma free Valproic acid concentration (r=0.76, p<0.018). In conclusion, saliva samples can be used as a substitute for plasma samples in the therapeutic drug monitoring of Valproic acid.
Keywords: therapeutic drug monitoring; salivary excretion classification system; valproic acid